On the risk of hydraulic fracturing in CO2 geological storage. (10th February 2016) - Papanastasiou, Panos; Papamichos, Euripides; Atkinson, Colin
Summary: We present a contribution on the risk of hydraulic fracturing in CO2 geological storage using an analytical model of hydraulic fracturing in weak formations. The work is based on a Mohr–Coulomb dislocation model that is extended to account for material with fracture toughness. The complete slip process that is distributed around the crack tip is replaced by superdislocations that are placed in the effective centers. The analytical model enables the identification of a dominant parameter, which defines the regimes of brittle to ductile propagation and the limit at which a mode‐1 fracture cannot advance. We examine also how the corrosive effect of CO2 on rock strength may affect hydraulic fracture propagation. We found that a hydraulically induced vertical fracture from CO2 injection is more likely to propagate horizontally than vertically, remaining contained in the storage zone. The horizontal fracture propagation will have a positive effect on the injectivity and storage capacity of the formation. The containment in the vertical direction will mitigate the risk of fracturing and migration of CO2 to upper layers and back to the atmosphere. Although the corrosive effect of CO2 is expected to decrease the rock toughness and the resistance to fracturing, the overall decrease of rock strength promotes ductile behavior with the energy dissipated in plastic deformation and hence mitigates the mode‐1 fracture propagation. Copyright © 2016 John Wiley & Sons, Ltd.